Assessment of cadmium and lead content in tomatoes and tomato products - Elżbieta Grochowska-Niedworok; Joanna Nieć; Renata Baranowska (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Cadmium and lead are completely redundant in the human body and any amount of these elements ingested poses a risk of adverse health effects. In non-occupational exposure the highest amount of xenobiotics enters the body with food. Valued for their taste, universal culinary application and health benefits tomatoes and tomato products are consumed almost every day by a large proportion of society. In order to protect consumers' health it is very important to monitor cadmium and lead content in food products. Objective. The aim of the study was the health assessment of cadmium and lead content in tomatoes and tomato products in relation to their acceptable maximum levels in the relevant legislation. Material and methods. Fresh fruits of the tomato plant and tomato products (juices, purées, concentrates, sauces) were analysed. Heavy metal content (Cd, Pb) was determined by flameless atomic absorption spectrometry (AAS). Before the AAS determination the samples were subjected to pressure mineralisation using microwave energy. Results. Cadmium and lead contents in the studied food products were within the allowed range (the maximum level of cadmium and lead contamination of tomatoes is 0.05 mg/kg and 0.1 mg/kg of fresh mass). The limit for cadmium was exceeded only in a canned tomato concentrate (0.064 mg/kg of fresh mass). The average cadmium content in raw tomatoes and tomato products was: 0.017 mg/kg fresh weight, and lead 0.021 mg/kg fresh weight. Conclusions. Despite the low cadmium and lead contamination of the study samples of tomatoes and tomato products, it seems desirable to constantly monitor the content of these elements in food due to their ability to accumulate in the body and the risk of adverse health effects developing after many years of exposure, even to small doses.